Sensorineural Hearing Impairment and Subclinical Atherosclerosis in Rheumatoid Arthritis Patients Without Traditional Cardiovascular Risk Factors - Hector MACIAS-REYES; Sergio DURAN-BARRAGAN; Cynthia R. CARDENAS-CONTRERAS; Cesar G. CHAVEZ-MARTIN; Eduardo GOMEZ-BAÑUELOS; Rosa E. NAVARRO-HERNANDEZ; Carlos O. YANOWSKY-GONZALEZ; Laura GONZALEZ-LOPEZ; Jorge I. GAMEZ-NAVA; Monica VAZQUEZ-DEL MERCADO (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the association of hearing impairment with carotid intima-media thickness and subclinical atherosclerosis in rheumatoid arthritis (RA) patients. Patients and methods: A total of 41 RA patients (2 males, 39 females; mean age 46.5±10.2 years; range 20 to 63 years) with no known traditional cardiovascular risk factors were included. Routine clinical and laboratory assessments for RA patients were performed. Pure tone air (250-8000 Hz) and bone conduction (250-6000 Hz) thresholds were obtained, tympanograms and impedance audiometry were conducted. Sensorineural hearing impairment was defined if the average thresholds were ≥25 decibels. Carotid intima-media thickness was assessed and classified with a cut-off point of 0.6 mm. Results: Thirteen patients (31.7%) had normal audition, while 28 (68.3%) had hearing impairment. Of these, 22 had bilateral sensorineural hearing impairment. Four patients had conductive hearing impairment (right in three patients and left in one patient). Patients with sensorineural hearing impairment had increased carotid intima-media thickness in the media segment of carotid common artery compared to patients with normal hearing (right ear p=0.007; left ear p=0.075). Thickening of the carotid intima-media thickness was associated with sensorineural hearing impairment in RA patients. Conclusion: Rheumatoid arthritis patients should be evaluated by carotid intima-media thickness as a possible contributing factor of hearing impairment in patients without cardiovascular risk factors.